A história e sua sombra: o problema da história entre Dilthey e Heidegger - Galdino Trindade , Rogerio (2020)
The work seeks to bring the “historical question” to the horizon of a philosophical reflection, that is, to recognize in “historicity [Geschichtlichkeit]” the fundamental scope of questioning what is properly historical. “Historicity” is the possibility of updating oneself of being as historical being-there. The term coined by Martin Heidegger from the German word “Geschichte” (History) is different from the common Germanic use of the word as a synonym for “Historie” (historiography/historical science). With the word "historicity", Heidegger points to what makes up the possibility of essential articulation of our historical condition of being in a world. It is not just because we make history books that we have a history ourselves. Rather, we are historical because we are faced with a reality that, in a way, was inherited, but that opens up as future possibilities to be continued, elaborated or overcome, that is, appropriate or not. Consequently, history must be considered from its essential scope, that is, to appear as the foundation of being launched proper to the human being in a destination. Unlike simple factual science, history, as a fundamental constituent of each of us, historical beings, is a form of time experience that updates us and launches us into the proper and inappropriate possibilities of our existence. Thus, in the present work, we limit ourselves to an introductory conceptual articulation of the historical question of being in the thoughts of Wilhelm Dilthey and Martin Heidegger.